Owning or being? The Evolving Meaning of Luxury and COVID-19 Pandemic. Sociological Research of Polish Society - Pawel KOSSECKI; Dominika NAROZNA; Agnieszka SMEKTALA; Karolina PLONECZKA; William STEINGARTNER (Communications of International Proceedings, 2021)
The global luxury market demonstrates a strong increase over the decades. Over the past years, luxury holdings started to move from the production of luxury goods to hospitality, leisure and travel. Luxury does not only mean perfected handcrafting but also lifestyle, values and memorable experiences. Especially younger generation is not so interested in the possession of goods. Rich consumers move from owning to being. They start to care much more about ethics, sustainability, spiritual development and self-actualization needs. For some customers, luxury means security, time for family, health and trust. For the others, luxury is a state of mind, migrating from concrete to abstract. People attend different aspects of what we call luxury. The authors surveyed respondents on one of the emerging luxury markets (Poland) before the coronavirus pandemic. The survey shows that the most important indicator of luxury in Poland is free time, less important are material assets and money. The most important intangible object considered in categories of luxury is love, followed by inner peace of mind, and children. Women attach more importance to the possession of luxury goods than men. The second survey was performed, when the coronavirus pandemic started. The same survey showed that generally, an important indicator of luxury for the respondents is now money and material asset. The most significant tangible object is again having a beautiful and healthy body and the most valid intangible objects are love and inner peace of mind, and children. We focus on this change of views on luxury and the importance of the criteria.
Keywords: Luxury; Meaning of Luxury; Intangible Luxury; Coronavirus pandemic; COVID-19